Karakteristik Buah dan Biji Kakao (Theobroma Cacao L.) pada Berbagai Altitude di Dataran Tinggi Dairi - Sitohang, Nurdin; Marbun, Arjun (LPPM Universitas Katolik Santo Thomas Medan, 2024)
The cocoa productivity is currently quite low quantity (454 kg ha-1) and quality, one of it caused by planting location of various altitude especially the highlands. The focus of this research were characteristic of cocoa pod and beans on several altitudes in Dairi highland. The research method were survey as purposive sampling on four altitudes as 860, 940, 1040, and 1120 m from sea levels (asl). The observed parameters were pod size, pod diametre, pod volume, dry weight of pod, dry weight of kolven, dry weight of beans, bean count per pod, dry weight per bean, pods value, and bean yield at 4 different altitudes in Dairi highland (>800 m asl) with 10 pods (replications) at each altitudes. The results of research showed that the increasing of altitude caused the decresed of pod size, pod diametre, pod dry weight, dry weight of beans, bean count per pod, dry weight each bean, pod value, and bean yield. The best pods and beans were at altitude of 860 m asl, namely fruit length 18.3 cm, fruit dry weight 118.6 g, beans dry weight 48.3 g, number of beans per fruit 43.7 and average weight per bean 1.10 g. The physical characteristics of cocoa pods and beans are still in the normal category.